Mapping open dumps and waste dynamics in a subtropical ecoregion of Argentina - Agustina Malizia; Alberto Galindo-Cardona; Emiliano Matias; Patricio Gallardo García Freire; Javier Foguet; A. Carolina Monmany-Garzia (Scientific Reports)
Abstract The proliferation of plastic waste since the 20th century has exacerbated pollution problems despite technological advances in waste management. In Argentina, 35% of municipal solid waste is discarded in untreated open dumps, causing environmental and public health risks. This study focused on detecting and mapping open dumps in the most densely populated province, Tucumán, using satellite imagery and unmanned aerial vehicles (UAV). Specifically, for each dump we (1) described spatio-temporal dynamics, (2) analyzed topography and hydrology characteristics, and (3) quantified waste mass. We identified and mapped forty open dumps (range size: 0.05 to 3.79 hectare). Most dumps were located within an endorheic basin, at 5 km or less from urban centers. Many have increased in size over the last decade, especially larger dumps (> than 1 hectare). The hydrological analysis showed material movement from dumps to surrounding environments, mainly watercourses and crops. Total waste mass averaged 5.72 kilotons (kt) per dump (range: 0.06 to 38.45 kilotons, where 1 kt = 1000 tons). This exhaustive survey of open dumps highlights the urgent need for sustainable waste management practices to mitigate environmental and public health risks in Tucumán and other regions facing similar challenges.